Development of status monitoring for routers and switches / Hairul Redzuan Saring - Saring, Hairul Redzuan (2007)
Status Monitoring for Routers and Switches (SMART) is a web based system which can display the status of all routers and switches that connected within the UiTM Shah Alam’s internal network. The system will give an iconic status representative by displaying green light or red light for each device. Red light means the devices are down and green light means the devices are in the fully working state. The system also provides an easy access for remote telnet operation. The main objective of SMART is to provide a graphical interface for the entire routers and switches that connected to the network. This application also provides a real time status to ease the monitoring process done by the system administrator. The method for keeping the system make a contact with the routers and switches is by sending an ICMP request to each device. If the device is running without a problem, it will automatically reply the ICMP packet to the system and with this method the system can keep track for the status of the devices